An Egyptian HPAI H5N1 isolate from clade 2.2.1.2 is highly pathogenic in an experimentally infected domestic duck breed (Sudani duck). Issue 3 (24th January 2018) - Samir, M.; Hamed, M.; Abdallah, F.; Kinh Nguyen, V.; Hernandez‐Vargas, E. A.; Seehusen, F.; Baumgärtner, W.; Hussein, A.; Ali, A. A. H.; Pessler, F.
Summary: The highly pathogenic avian influenza (HPAI) H5N1 viruses continue to cause major problems in poultry and can, although rarely, cause human infection. Being enzootic in domestic poultry, Egyptian isolates are continuously evolving, and novel clades vary in their pathogenicity in avian hosts. Considering the importance of domestic ducks as natural hosts of HPAI H5N1 viruses and their likelihood of physical contact with other avian hosts and humans, it is of utmost importance to characterize the pathogenicity of newly emerged HPAI strains in the domestic duck. The most recently identified Egyptian clade 2.2.1.2 HPAI H5N1 viruses have been isolated from naturally infected pigeons, turkeys and humans. However, essentially nothing is known about their pathogenicity in domestic ducks. We therefore characterized the pathogenicity of an Egyptian HPAI H5N1 isolate A/chicken/Faquos/amn12/2011 (clade 2.2.1.2) in Sudani duck, a domestic duck breed commonly reared in Egypt. While viral transcription (HA mRNA) was highest in lung, heart and kidney peaking between 40 and 48 hpi, lower levels were detected in brain. Weight loss of infected ducks started at 16 hpi and persisted until 120 hpi. The first severe clinical signs were noted by 32 hpi and peaked in severity at 72 and 96 hpi. Haematological analyses showed a decline in total leucocytes, granulocytes, platelets and granulocyte/lymphocyte ratio, but lymphocytosis. Upon necropsy, lesions were obvious in heart, liver, spleen and pancreas and consisted mainly of necrosis and petechial haemorrhage. Histologically, lungs were the most severely affected organs, whereas brain only showed mild neuronal degeneration and gliosis at 48 hpi despite obvious neurological clinical signs. Taken together, our results provide first evidence that this HPAI H5N1 isolate (clade 2.2.1.2) is highly pathogenic to Sudani ducks and highlight the importance of this breed as potential reservoir and disseminator of HPAI strains from this clade.